2023
DOI: 10.3390/neurolint15010022
|View full text |Cite
|
Sign up to set email alerts
|

Protein Metabolism Changes and Alterations in Behavior of Trace Amine-Associated Receptor 1 Knockout Mice Fed a High-Fructose Diet

Abstract: Trace amines and their receptors are a family of G protein-coupled receptors widely distributed in the central nervous system and periphery. The trace amine-associated receptor 1 (TAAR1) plays a significant role as a therapeutic target for schizophrenia, depression, diabetes, and obesity. In this study, TAAR1 knockout mice and WT groups were tested in conditions of a high-fructose diet. The consumption of a high-fructose diet may be due to the influence on the metabolism processes by dopamine in the brain, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…The TAAR1 agonist RO5166017 stimulates SST production in stomach D-cells and this effect seems to be TAAR1 dependent [136]. Also, it was identified that TAAR1 gene knockout in mice is associated with an increase in catabolic reaction, although the basis of this association is not described yet [138].…”
Section: Background and Prospects For The Clinical Use Of Trace Amine...mentioning
confidence: 99%
“…The TAAR1 agonist RO5166017 stimulates SST production in stomach D-cells and this effect seems to be TAAR1 dependent [136]. Also, it was identified that TAAR1 gene knockout in mice is associated with an increase in catabolic reaction, although the basis of this association is not described yet [138].…”
Section: Background and Prospects For The Clinical Use Of Trace Amine...mentioning
confidence: 99%